Cat scratch disease sepsis in an immunocompromised patient. Issue 7 (13th July 2021) - James, Sunil; Thozhuthumparambil, Karunakaran Pradeep
Abstract : As a greater number of households have pets, the likelihood of zoonotic infections can rise too. Although in most healthy individuals these infections are self-limiting, they are more serious and can lead to adverse outcomes in the immunocompromised. There is minimal information available for the immunocompromised patient who are pet owners or on pet handling. We report a case of cat scratch disease-related sepsis in an immunocompromised patient. This case illustrates the need for a detailed history, including a pet history, in immunocompromised patients presenting with fever of unknown origin and the need for UK-based information for the immunocompromised on pet care and risks associated with having a pet.